Abordagens estatísticas em testes de resistência de união entre dentina bovina, sistema adesivo e resina composta - Balducci, Ivan [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The aim of this study was to use different statistical approaches on data obtained from micro and macrotensile tests in two periods of time storage, in order to describe and quantify the variability commonly found in adhesion tests. 48 bovine teeth were selected. The roots were sectioned 2 mm below the cement-enamel junction and the buccal surfaces were ground to exposure a dentin flat surface. The teeth were embedded in acrylic resin and randomly assigned to four groups (n = 12) to evaluate the bond strength (BS). For the microtensile test the adhesive Adper Single Bond 2 - (2 SE Bond - 3M - ESPE) was applied in an area of 8 mm2, followed by air jet during 2 to 5 s and curing for 15 s. Right after the XT - Z350 composite resin (3M ESPE) was inserted. After 24 h of storage in distilled water at 37 °C, for each tooth a variable number of sticks was obtained. Twelve teeth were submitted to microtensile test after 24 h (G1) and other 12 to thermocycling (G2) and microtensile test. For macrotensile, the smallest base of conical shape specimens was 2 mm. After 24 h twelve samples were subjected to macrontesile test (G3) and the other twelve, after 24 h, were thermocycled (G4). The data were submitted to an exploratory analysis, followed by a (inferential) confirmatory analysis. Descriptive statistics and the results of Weibull analysis for the data of BS (MPa) of the experimental conditions were: G1 (module; mean ± standard deviation: 2.54; 10.76 ± 4.21); G2 (3.36; 19.34 ± 6.42); G3 1.96; 3.17 ± 1.51; G4 (1.75; 2.86 ± 1.68). The ANOVA (2-way), α = 5%, indicated significant interaction effect, and Tukey tests and Dunn (5%), complemented the results. The conclusion is: the different statistics strategies (Weibull analysis, exploratory analysis and parametric approach) showed the same results, namely the existence of the aging effect only for the microtensile bond; in the comparison betw...

O objetivo deste estudo foi empregar diferentes abordagens estatísticas em dados obtidos em ensaios de micro e macrotração, em dois períodos de tempo de armazenamento, a fim de descrever e quantificar a variabilidade comumente encontrada nos testes de adesão. Foram selecionados 48 dentes bovinos. As raízes seccionadas a 2 mm abaixo da junção cementoesmalte e as faces vestibulares foram desgastadas expondo superfície de dentina plana. Os dentes foram embutidos em resina acrílica e aleatoriamente designados a quatro grupos (n = 12) para avaliação da resistência de união (RU). Para o teste de microtração foi aplicado o adesivo Adper Single Bond 2- (SE Bond 2- 3M-ESPE) numa área de 8 mm2, seguido de jato de ar por 2 a 5 s e fotopolimerização por 15 s e, a seguir, inserida a resina composta Z350 XT- (3 M-ESPE). Após 24 h de armazenamento, em água destilada a 37 ºC, para cada dente um número variável de palitos foi obtido. Doze dentes foram submetidos ao teste de microtração após 24 h (G1) e outros 12 submetidos à termociclagem (G2) seguido de microtração. Para a macrotração, a base menor dos espécimes cônicos foi de 2 mm. Doze amostras após 24 h foram submetidas ao teste de macrotração (G3) e as outras doze, após as 24 h, termocicladas (G4). Os dados foram submetidos a uma análise exploratória; seguidos de uma análise confirmatória (inferencial). A estatística descritiva e o resultado da análise de Weibull para os dados de RU (MPa) foram: G1(módulo; média ± desvio padrão: 2,54; 10,76 ± 4,21); G2 (3,36; 19,34 ± 6,42); G3 (1,96; 3,17 ± 1,51; G4 (1,75; 2,86 ± 1,68). O teste ANOVA (2-way), α = 5%, indica efeito interação significante e, os testes de Tukey e de Dunn (5%), complementaram os resultados. Pôde-se concluir: as diferentes estratégias estatísticas (análise de Weibull, análise exploratória e abordagem paramétrica) indicaram os mesmo resultados. Pode-se concluir: as diferentes...
Keywords: Materiais dentários; Adesivos dentarios; Estatística; Statistics